2014
DOI: 10.1016/j.parint.2013.07.011
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging of trypanosomes for a better assessment of host–parasite relationships and drug efficacy

Abstract: The advances in microscopy combined to the invaluable progress carried by the utilization of molecular, immunological or immunochemical markers and the implementation of more powerful imaging technologies have yielded great improvements to the knowledge of the interaction between microorganisms and their hosts, notably a better understanding of the establishment of infectious processes. Still today, the intricacies of the dialog between parasites, cells and tissues remain limited. Some improvements have been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Additionally, various strains of parasites have varied tissue tropisms, particularly with different MHC restricted murine hosts [4] , [27] . To overcome some of these issues, luciferase expressing parasites have been developed as tools for drug discovery [28] , [29] . Recent data has demonstrated that T. cruzi parasites progressively migrate to, and infect different organs of the host, with the gastro-intestinal tract being the major reservoir of infection in the chronic phase [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, various strains of parasites have varied tissue tropisms, particularly with different MHC restricted murine hosts [4] , [27] . To overcome some of these issues, luciferase expressing parasites have been developed as tools for drug discovery [28] , [29] . Recent data has demonstrated that T. cruzi parasites progressively migrate to, and infect different organs of the host, with the gastro-intestinal tract being the major reservoir of infection in the chronic phase [29] .…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence of the usefulness of fluorescent/luminescent reporters in preclinical studies targeting trypanosomatid-borne Drug Discovery Today Volume 20, Number 1 January 2015 REVIEWS T. vivax P. pyralis luciferase AAT (Nagana) Method validation [61] diseases. The use of such modified strains introduces many advantages compared with conventional methods, including: (i) in vivo imaging enables the study of freshly dissected tissues from an infected animal where parasites can be individually identified; (ii) it also enables one to develop easily new platforms for the screening of potential new drugs by analysing libraries of thousands of compounds against trypanosomatids; therefore, it could be an effective alternative to the tedious and time-consuming staining methods; (iii) it is a sensitive real-time tool to investigate the development of an infection, especially during the earlier phases of the infectious process; (iv) it can be used as a complementary phenotypic biomarker to evaluate the genetic exchange occurrence in these pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…There are several other cases of conceptual breakthroughs that we did not cover in this review on microscopy, including newly developed techniques that could certainly lead to important changes in how we conceptualize similar intracellular parasites. Namely, electron tomography in cryopreserved samples allows for 3D reconstruction of infected cells and parasites bypassing cumbersome serial slicing; superresolution microscopes (PALM/STORM and STED) increase optical resolution to tens of nanometers and allow for live imaging; bioluminescent parasites could be tracked in whole organisms using in vivo bioluminescent imaging systems [117, 118]; and use of reporters, probes, or other microcopy techniques (FRAP, FRET and FLIM) improves microscopic observations regarding biochemical/molecular mechanisms of host/pathogen interactions. We can rely on history to repeat itself in that further studies using these cutting-edge microscopic technologies will change our perception of Leishmania spp.…”
Section: Discussionmentioning
confidence: 99%